2019
DOI: 10.1002/ptr.6555
|View full text |Cite
|
Sign up to set email alerts
|

The regulation and interaction of colon cancer‐associated transcript‐1 and miR7‐5p contribute to the inhibition of SP1 expression by solamargine in human nasopharyngeal carcinoma cells

Abstract: Nasopharyngeal carcinoma (NPC) is a common head and neck malignancy with higher incidence in Southern China and Southeast Asia. Solamargine (SM), a steroidal alkaloid glycoside, has been shown to have anticancer properties. However, the underlying mechanism involved remains undetermined. In this study, we showed that SM inhibited the growth of NPC cells. Mechanistically, we found that solamargine decreased lncRNA colon cancer-associated transcript-1 (CCAT1) and increased miR7-5p expression. There was a recipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
(57 reference statements)
0
18
0
Order By: Relevance
“… 21 A recent study showed that exogenous SP1 could inhibit the expression of miR7-5p and could reverse the growth of NPC cells inhibited by solamargine. 22 Ho et al. 23 found that melatonin can regulate the expression of matrix metalloprotein 9 (MMP-9) gene induced by tumor promoter 12-o-tetradecanoylphosphate-3-acetate (TPA) by inhibiting the binding ability of SP1 to DNA, thus inhibiting the metastasis activity of NPC.…”
Section: Discussionmentioning
confidence: 99%
“… 21 A recent study showed that exogenous SP1 could inhibit the expression of miR7-5p and could reverse the growth of NPC cells inhibited by solamargine. 22 Ho et al. 23 found that melatonin can regulate the expression of matrix metalloprotein 9 (MMP-9) gene induced by tumor promoter 12-o-tetradecanoylphosphate-3-acetate (TPA) by inhibiting the binding ability of SP1 to DNA, thus inhibiting the metastasis activity of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…BEC is active against a wide variety of cancer cells, such as ovarian cancer [30], basal cell carcinoma [31], squamous cell carcinoma [32], melanoma [33], colorectal cancer [34], bladder cancer [35], oral epidermoid carcinoma [36], breast cancer [25], leukemia [37], prostate cancer [38], liver cancer [39], lung cancer [40], pancreatic cancer [41], gastric carcinoma [23], renal cancer [31], uterine cancer [30], mesothelioma [42], glioblastoma [43] and osteosarcoma [19]. In addition, BEC has curative properties in animals with terminal cancer [4] [12].…”
Section: Becmentioning
confidence: 99%
“…Solamargine (SM), a natural sugar alkaloid extracted from the fruits of Solanaceae plants, has been fully confirmed by our previous studies and other reports that SM can significantly inhibit the occurrence and development of a variety of cancers. [4][5][6][7] The growing number of studies have found that SM exhibits its antitumor activity through multifarious pathways, including tumor growth pathways, apoptosis-related pathways, mitochondrial pathways, protein kinase pathways, and so on. 8 For example, SM significantly suppresses the expression of X-linked apoptosis inhibitor, PCNA, and cyclin D1, while increasing the activity of caspase-3 to induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%